PRACTITIONERS’ PERCEPTION ON THE ROLEs OF MARKETING CONSULTANTS IN DEVELOPING COMPETITIVE INTELLIGENCE IN NIGERIAN SMEs - EBERE, OKOCHA REJOICE; NNAMCHI, CHRI-; NWAKAEGO, JOY; VICTORIA, IKABA YIRAKPOA (IJRDO - Journal of Business Management, 2017)
this study focused on Practitioners’ Perception on the Roles of Marketing Consultants in Developing Competitive Intelligence in Nigerian SMEs. The researchers used descriptive survey tool (questionnaire) to gather data from 60 firms which consists of 45 small and medium scale enterprises and 15 marketing consultants selected from the five south-eastern states of Nigeria (Abia, Anambra, Ebonyi, Enugu and Imo State). The total population for this study was 702 members of staff of both the SMEs and the marketing consulting firms; however, purposive sampling technique was used to draw a sample of 150 respondents from the population. The data gathered were then analyzed using kruskawalis test (H) and the pearson product moment correlation (PPMC) with the aid of 20.0 version of SPSS. The study concludes that the challenge of competitive intelligence of Nigerian SMEs can be solved through the proper and timely engagement of marketing consultants either through direct recruitment of marketing professionals and establishment of marketing research unit who will be charged among other things with the responsibility of gathering, classifying, storing and making available relevant and current information on competitors and other market dynamics for strategic decision making. The researchers advocate a more serious engagement of marketing consultants by SMEs in order to develop their competitive intelligence which will drive their profitability and sustainability. It was also recommended that government through some of their agencies like SMEDAN can avail SMEs such service in order to share the burden of cost involved in competitive intelligence development